2018
DOI: 10.1371/journal.pone.0194864
|View full text |Cite
|
Sign up to set email alerts
|

Validity of consumer-grade activity monitor to identify manual wheelchair propulsion in standardized activities of daily living

Abstract: BackgroundHypoactive lifestyle contributes to the development of secondary complications and lower quality of life in wheelchair users. There is a need for objective and user-friendly physical activity monitors for wheelchair-dependent individuals in order to increase physical activity through self-monitoring, goal setting, and feedback provision.ObjectiveTo determine the validity of Activ8 Activity Monitors to 1) distinguish two classes of activities: independent wheelchair propulsion from other non-propulsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…The vector counts were used to perform the classification. Classification was performed using custom-written Matlab algorithms, which were validated for detecting independent wheelchair propulsion [9]. Each epoch was classified either as independent wheelchair propulsion (propulsion as a result of arm power of the participant) or as other activity (including but not limited to: being pushed in the wheelchair, reaching movements, general upper body motions).…”
Section: Mechanical Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…The vector counts were used to perform the classification. Classification was performed using custom-written Matlab algorithms, which were validated for detecting independent wheelchair propulsion [9]. Each epoch was classified either as independent wheelchair propulsion (propulsion as a result of arm power of the participant) or as other activity (including but not limited to: being pushed in the wheelchair, reaching movements, general upper body motions).…”
Section: Mechanical Efficiencymentioning
confidence: 99%
“…Each epoch was classified either as independent wheelchair propulsion (propulsion as a result of arm power of the participant) or as other activity (including but not limited to: being pushed in the wheelchair, reaching movements, general upper body motions). A given epoch was classified as independent wheelchair propulsion if the wheel counts were contained between 31 and 310 counts or if they exceeded 310 and at the same time wrist counts exceeded 98 [9]. In all other cases, an activity was classified as "other".…”
Section: Mechanical Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Inertial Measurement Units (IMUs) are easier to use, but, when wrist-applied as typical practice [ 4 ] lack detailed joint kinematics at the shoulder, a key joint in assessing injury risk for manual wheelchair users. Leving et al [ 5 ] has shown promise for IMUs to detect spatiotemporal parameters of motion, including activity level, but does not describe movement kinematics. Similarly, van der Slikke et al [ 6 9 ] have shown accurate measurements by IMUs in speed, displacement, and acceleration metrics applied to wheelchair sports.…”
Section: Introductionmentioning
confidence: 99%
“…Their use during daily activities and training activities in particular is unpractical. Physical activity monitors were able to distinguish between active wheelchair propulsion and other nonpropulsive wheelchair-related activities in a laboratory setting [16]. Compliance in long-term use to monitor daily activities in free-living conditions, including training activities has been a problem in previous research on accelerometers, as well as activity monitors in behavioral change programs in people with SCI [17].…”
Section: Introductionmentioning
confidence: 99%